2021
DOI: 10.1111/1747-0080.12654
|View full text |Cite
|
Sign up to set email alerts
|

Key concepts for dietetic curriculum: An observational study of Australian dietitians' perceptions

Abstract: Aim A concept‐based approach to dietetic curriculum design has been proposed to prevent content overload and promote critical thinking. Fifty‐six concepts were identified in a previous study. The aim of the present study was to investigate whether the dietetic profession views these concepts as representative of current practice and key for nutrition and dietetics education, and identify any new or emerging concepts. Methods Accredited Practising Dietitians (APDs) were invited to participate in a self‐administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…5 It is time to define a unified nutrition and dietetics profession, which works together to develop as food aficionados, diet optimisers, knowledge translators, equity champions, systems navigators and food systems activists, change makers, activists and disruptors. Education providers may benefit from considering concept-based approaches 35 as they consider transformation of curricula to meet these needs.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is time to define a unified nutrition and dietetics profession, which works together to develop as food aficionados, diet optimisers, knowledge translators, equity champions, systems navigators and food systems activists, change makers, activists and disruptors. Education providers may benefit from considering concept-based approaches 35 as they consider transformation of curricula to meet these needs.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour change science was viewed as fundamental to dietetics with some participants reporting they wanted to add behaviour change science content but felt their curriculum was already overloaded. The use of concept‐based approaches, which are “mental constructs of one or two‐word nouns, or short phrases”, 26 (p2) would allow behaviour change science content to be added without overloading curricula. Some participants expressed a lack of confidence in teaching behaviour change science.…”
Section: Discussionmentioning
confidence: 99%
“…2 In 2020, the present authors reported on Australian dietitians' views of 56 core concepts required for the practice of nutrition and dietetics and found that greater than 65% of respondents agreed that these concepts were relevant for education and current practice. 3 As concepts are mental constructs that are timeless, universal and abstract, and have examples that share common attributes, 4 it could be surmised that these concepts would not significantly change over time. What does change, however, are the exemplars that demonstrate how the concept would apply in dietetics which may change depending on changing health priorities or workforce needs.…”
mentioning
confidence: 99%